Increasing Financial Literacy With “Moma” Money Management Learning Media In Vocational High Schools: Meningkatkan Literasi Keuangan Dengan Media Pembelajaran “Moma” Money Management Di Sekolah Menengah Kejuruan - Saputri, Agatha; Nurrahman, Arief; Zylio Nugraha, R. Andro; Rosyad Achmadi, Caesar; Harfiansyah Makarim, Muhammad; Murti Sagoro, Endra (Universitas Negeri Yogyakarta, 2025)
Financial literacy is one of the essential life skills that must be possessed by every individual, especially vocational students. However, financial learning media used in schools tend to be conventional and not interactive. Therefore, innovation is needed in the form of interactive learning media that can present relevant, interesting, and applicable learning experiences. This research is development research (R&D) that aims to improve the financial literacy of Vocational High School students through the development of